Peer Assessment in Medical Student Education: A Study of Feasibility, Benefit, and Worth. Issue 9 (September 2022) - DuCoin, Christopher; Zuercher, Hannah; McChesney, Shannon L.; Korndorffer, James R.
Background: Direct experience with medical procedures is an important component of medical school training, yet opportunities for medical students have dwindled for various reasons. To offset this, simulated procedures are being integrated into training. However, this comes with additional time commitments required of teaching surgeons regarding assessment of simulation. A solution to this could be peer assessment. We hypothesize that there will be no significant difference between peer assessment when compared to that of a teaching surgeon. Methods: Third-year medical students were shown 3 simulated procedures by teaching surgeon and provided a grading rubric. Student performances were independently graded by peer assessment and by teaching surgeons. All peer assessment grades and surgeon grades were compared. Results: Four hundred fifty-nine medical students completed the simulation procedures. Comparisons between the teaching surgeons and peer assessment evaluations demonstrated a 99% interobserver agreement for pass-fail designation and 98% agreement for individual data points (kappa = .78). Survey results demonstrated a significant increase in confidence in performing the tested items and comfort with peer assessment. Discussion: This analysis demonstrates that the inclusion of peer assessment within medical school is highly comparable to teaching surgeon assessments.